Time-resolved momentum imaging system for molecular dynamics studies using a tabletop ultrafast extreme-ultraviolet light source - Gagnon, Etienne; Sandhu, Arvinder S.; Paul, Ariel; Hagen, Kim; Czasch, Achim; Jahnke, Till; Ranitovic, Predrag; Lewis Cocke, C.; Walker, Barry; Murnane, Margaret M.; Kapteyn, Henry C. (My University, 2008)
We describe a momentum imaging setup for direct time-resolved studies of ionization-induced molecular dynamics. This system uses a tabletop ultrafast extreme-ultraviolet (EUV) light source based on high harmonic upconversion of a femtosecond laser. The high photon energy (around 42eV) allows access to inner-valence states of a variety of small molecules via single photon excitation, while the sub-–10-fs pulse duration makes it possible to follow the resulting dynamics in real time. To obtain a complete picture of molecular dynamics following EUV induced photofragmentation, we apply the versatile cold target recoil ion momentum spectroscopy reaction microscope technique, which makes use of coincident three-dimensional momentum imaging of fragments resulting from photoexcitation. This system is capable of pump-probe spectroscopy by using a combination of EUV and IR laser pulses with either beam as a pump or probe pulse. We report several experiments performed using this system.